2019
DOI: 10.1016/j.atherosclerosis.2019.01.034
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-cyclodextrin inhibits cholesterol crystal-induced complement-mediated inflammation: A potential new compound for treatment of atherosclerosis

Abstract: Background and aims: Cholesterol crystal (CC)-induced inflammation is a critical step in the development of atherosclerosis. CCs activate the complement system and induce an inflammatory response resulting in phagocytosis of the CCs, production of reactive oxygen species (ROS) and release of cytokines. The cyclodextrin 2-hydroxypropyl-β-cyclodextrin has been found to reduce CC-induced complement activation and induce regression of established atherosclerotic plaques in a mouse model of atherosclerosis, thus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…The time-dependent findings are also in line with experiments reported by Pilely et al . and Ding et al ., that show that while incubation of different types of cyclodextrin for a short period of time (10 and 30 min) is anti-inflammatory ( 35 ), incubation for 24 and 48hr lead to ototoxicity ( 19 ). Together, these observations indicate that while CD has potential in advantageously depleting cellular cholesterol, it is essential to monitor the quantity of cellular cholesterol and adjust the therapeutic dose/time accordingly to prevent undesired pro-inflammatory side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…The time-dependent findings are also in line with experiments reported by Pilely et al . and Ding et al ., that show that while incubation of different types of cyclodextrin for a short period of time (10 and 30 min) is anti-inflammatory ( 35 ), incubation for 24 and 48hr lead to ototoxicity ( 19 ). Together, these observations indicate that while CD has potential in advantageously depleting cellular cholesterol, it is essential to monitor the quantity of cellular cholesterol and adjust the therapeutic dose/time accordingly to prevent undesired pro-inflammatory side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that Mβ-CD and HPβ-CD reduce cholesterol accumulation [ 26 , 27 , 28 , 29 ]. Pilely et al, in 2019 discovered that α-CD and HPβ-CD can solubilize cholesterol crystals, reducing the complement-mediated inflammation by binding of C1q (via IgM) and ficolin-2 to cholesterol crystals, which resulted in reduced phagocytosis and reduced ROS production [ 30 ]. Moreover, different derivatives such as HPγ-CD (which cannot complex cholesterol) mobilize cholesterol; the treatment with HPγ-CD and HPβ-CD [ 31 ] induced the expression of protein-like LAMP-1, which is expressed in the lysosomal membrane.…”
Section: Cyclodextrin Monomers and Polymers As Drugs Themselvesmentioning
confidence: 99%
“…Pilely et al, in 2019, discovered that α-CD inhibits cholesterol crystal-induced complement-mediated inflammation better than HPβ-CD. It is even able to solubilize cholesterol crystals [ 65 ].…”
Section: Cyclodextrins As Active Drugsmentioning
confidence: 99%